Pengaruh Keterampilan Kerja dan Lingkungan Kerja Terhadap Produktivitas Kerja pada PT XYZ Balikpapan - Eva Berliana Siahaan; Siti Maria (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the effect of work skills and work environment on employee work productivity at PT XYZ Balikpapan. A quantitative approach was employed with a sample of 41 employees selected based on specific criteria. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression with the assistance of IBM SPSS Statistics version 27. The results indicate that work skills have a positive and significant effect on employee work productivity, highlighting the important role of individual capabilities in achieving optimal performance. In contrast, the work environment does not have a significant effect on work productivity, suggesting that it functions more as a supporting factor rather than a primary determinant of employee productivity.